Iron‐ and aluminium‐induced depletion of molybdenum in acidic environments impedes the nitrogen cycle. (21st November 2018) - Ge, Xiaoxuan; Vaccaro, Brian J.; Thorgersen, Michael P.; Poole, Farris L.; Majumder, Erica L.; Zane, Grant M.; De León, Kara B.; Lancaster, W. Andrew; Moon, Ji Won; Paradis, Charles J.; von Netzer, Frederick; Stahl, David A.; et al.
Summary: Anthropogenic nitrate contamination is a serious problem in many natural environments. Nitrate removal by microbial action is dependent on the metal molybdenum (Mo), which is required by nitrate reductase for denitrification and dissimilatory nitrate reduction to ammonium. The soluble form of Mo, molybdate (MoO4 2− ), is incorporated into and adsorbed by iron (Fe) and aluminium (Al) (oxy) hydroxide minerals. Herein we used Oak Ridge Reservation (ORR) as a model nitrate‐contaminated acidic environment to investigate whether the formation of Fe‐ and Al‐precipitates could impede microbial nitrate removal by depleting Mo. We demonstrate that Fe and Al mineral formation that occurs as the pH of acidic synthetic groundwater is increased, decreases soluble Mo to low picomolar concentrations, a process proposed to mimic environmental diffusion of acidic contaminated groundwater. Analysis of ORR sediments revealed recalcitrant Mo in the contaminated core that co‐occurred with Fe and Al, consistent with Mo scavenging by Fe/Al precipitates. Nitrate removal by ORR isolate Pseudomonas fluorescens N2A2 is virtually abolished by Fe/Al precipitate‐induced Mo depletion. The depletion of naturally occurring Mo in nitrate‐ and Fe/Al‐contaminated acidic environments like ORR or acid mine drainage sites has the potential to impede microbial‐based nitrate reduction thereby extending the duration of nitrate in the environment.